HyProCure for Pediatric Flexible Flatfoot: What Affects the Outcome - Chen, Cheng; Jiang, JianTao; Fu, ShaoLing; Wang, Cheng; Su, Yan; Mei, GuoHua; Xue, JianFeng; Zou, Jian; Li, XueQian; Shi, ZhongMin (Frontiers in Pediatrics, 2022)
Background: The high success rate, minimally invasion and safety of subtalar arthroereisis (SA) have made it a primary mode of surgical management for pediatric flexible flatfoot. HyProCure procedure is a new surgery of subtalar arthroereisis, However, very few available studies reported therapeutic effects of HyProCure procedure, especially in pediatric flexible flatfoot. The main aim of the present study was to investigate the clinical and radiological outcomes of HyProCure procedure for pediatric flexible flatfoot, and analyze the risk factors for therapeutic outcomes and sinus tarsi pain. Methods: In this retrospective cohort study, 69 pediatric flexible flatfoot patients (107 feet) with HyProCure procedure were included between July 2015 and September 2020. All patients were performed HyProCure procedure combined with or without gastrocnemius recession. The Maryland foot score (MFS), visual analog scale (VAS), radiographic data and complications were assessed at a minimum 1 year follow-up and statistically analyzed. Results: The mean follow-up was 35.9 months (range, 13–73 months). At the last follow-up, VAS (0.64±1.16) was significantly lower than the preoperative VAS (4.06±1.43) (P<0.001); MFS (90.39±12.10) was significantly higher than the preoperative MFS (71.36±10.25) (P<0.001). The AP talar-second metatarsal angle (T2MT angle) significantly decreased from (17.0±5.4)° preoperatively to (11.4±5.2)° at the last follow-up (P<0.001). The lateral talar-first metatarsal angle (Meary’s angle) significantly decreased from (13.8±6.4)° preoperatively to (6.3±5.0)° at the last follow-up (P<0.001). The calcaneal declination angle (Pitch angle) significantly increased from (13.5±4.9)° preoperatively to (14.8±4.4)° at the last follow-up (P<0.001). Logistic regression analysis indicated that patients with a longer distance from the tail end of the implant exceeding the longitudinal talar bisection line had 275.8% greater odds of MFS<90. Yet, no risk factors were found in connection with sinus tarsi pain. Conclusions: HyProCure procedure for pediatric flexible flatfoot achieved satisfactory curative effects with low complication rate, implant depth was associated with unsatisfactory postoperative outcome.